Overcoming the calcification barrier: Enhanced power generation via acid pretreatment of calcified Pleurochrysis carterae biomass in membrane-less microbial fuel cells - Taskan, Banu; Taskan, Ergin; Ozkaya, Bestami (Elsevier Science Sa, 2027)
Calcified cell walls impose structural limitations on the bioelectrochemical use of Pleurochrysis carterae (P.car-terae), despite its high lipid content and CaCO3 biomineralization capacity. In this study, P.carterae biomass was pretreated with 1-3% (v/v) H2SO4 for 30 min and fed to the anode of a membrane-less microbial fuel cell. Acid pretreatment increased the maximum power density from 420 to 1130 mW m(-2), corresponding to approximately a 2.7-fold increase. Electrochemical analyses showed that this improvement was associated with a decrease in internal resistance, with ohmic and charge transfer resistances reduced by 78% and 90%, respectively. CV and EIS results supported enhanced electron transfer after acid pretreatment. Microbial community analysis revealed that electroactive genera such as Shewanella sp. and Desulfovibrio sp. became more abundant under highperformance conditions. Overall, these findings indicate that acid pretreatment alleviates charge-transfer limitations, improves bioelectrochemical performance, and highlight calcified microalgae as a promising biomass source for energy production and carbon management.
Keywords: Coccolithophore Microalgae; Pleurochrysis Carterae; Acid Pretreatment; Membrane-Less Microbial Fuel Cell; Charge Transfer Resistance; Bioelectricity Generation